UWAGI NA TEMAT ODPOWIEDZIALNOŚCI ‘MAGISTRATUS POPULI ROMANI’ W ŚWIETLE PRAWA PRYWATNEGO ORAZ PRAWA PUBLICZNEGO - Kołodko, Piotr (Zeszyty Prawnicze, 2016)
SOME REMARKS ON THE RESPONSIBILITY OF THE MAGISTRATUS POPULI ROMANI IN THE LIGHT OF PRIVATE AND PUBLIC LAW Summary The article presents the immunity process for the magistratus populi Romani on the grounds of ius privatum and ius publicum. In view of the source material which has been preserved this subject is generally discussed in terms of the magistratus maiores and magistratus minores (senior and junior magistrates). I show that under private law senior magistrates, who were vested with imperium, were protected against in ius vocatio summons during their term in office. On the other hand, their junior colleagues, the magistratus minores, who were equipped only with potestas, could be sued in the course of their term. Hence, they did not enjoy the warranty process which served the exclusive benefit of the senior magistrates of Republican Rome. Due to the profound evolution that Roman criminal proceedings underwent, a uniform approach to the issue of immunity against prosecution was never developed. The first successful attempt to introduce magistrates’ immunity has to be associated with the lex Acilia repetundarum, which had a limited scope: only senior magistrates and those junior magistrates who exercised the powers of imperium were its beneficiaries; also it only applied to the crimen repetundarum. The lex Memmia de absentibus, which was adopted in 113 BC, was not much more than a half-measure, but it definitely broadened the group of protected magistrates. It is difficult to determine whether it was treated as a general lex, applicable not only to the standing courts (quaestiones perpetuae) and to the extraordinary court (quaestiones extraordinariae), but also to the iudicia populi (the “people’s courts” or centuriate assemblies). However, it is most likely that the provisions of this lex applied to the extraordinary criminal courts, since the quaestiones perpetuae did not start operations until the late second century BC.